Uterine lipoma: A case report - Noni Chan; Mathumathi Vythianathan (Elsevier, 2020)
Uterine lipomas are a rare benign gynaecological tumour of uncertain histogenesis. Clinically, a uterine lipoma may be mistaken for leiomyoma or a malignant tumour. Radiological findings may be suggestive but can also often be inconclusive. However, it has a distinctive appearance on histopathological examination. We present a case of uterine lipoma in a 70-year-old woman, to increase awareness of this unusual entity.